HIERARCHY OF NEEDS ANALYSIS OF THE MAIN CHARACTER OF A NOVEL ENTITLED FLAWED BY CECELIA AHERN - Ronie, Fiana Isnaeni Maheda; Hellystia, Devi (Journal of Language and Literature, 2019)
This undergraduate thesis is entitled Hierarchy of Needs Analysis of The Main Character of A Novel Entitled Flawed By Cecelia Ahern. This study is intended to find out what are the hierarchy of needs that have been fulfilled by the main character and how the main character fulfilled the hierarchy of needs. The data were taken from the novel Flawed written by Cecelia Ahern. The researcher used qualitative and descriptive method in analyzing the hierarchy of needs. In this research, the researcher found 10 data of physiological needs, 34 data of physiological needs, 52 data of love and belonging needs, 44 data of self esteem, and 24 data of self actualization. Based on Maslow’s  theory, there are five level of hierarchy of needs that the main character can satisfied.